An observational study of Chinese adults with relapsed/refractory Philadelphia-negative acute lymphoblastic leukemia. (25th July 2018) - Ma, Jun; Liu, Ting; Jin, Jie; Hu, Jianda; Liu, Qifa; Wang, Jianxiang; Shen, Zhixiang; Du, Xin; Jiang, Bin; Meng, Xianhua
Aim: Chinese adults with relapsed/refractory Philadelphia chromosome-negative B-cell precursor acute lymphoblastic leukemia (Ph- ALL) have poor outcomes.Patients & methods: We conducted a nationwide, retrospective, observational study to assess outcomes in this patient population.Results: Of the 270 enrolled patients, 31% of patients at last salvage achieved complete remission (CR) or CR with partial hematologic recovery (CRh), with median time to CR/CRh of 30 days and median CR/CRh duration of 2.7 months. The CR/CRh rate was more favorable with earlier versus later lines of salvage (41, 24 and 17% at first, second and third or later salvages, respectively).Conclusion: This dataset serves as an important reference of real-world outcomes using currently available chemotherapy regimens for high-risk Chinese adults with relapsed/refractory Ph- ALL.